Fluoride removal efficiency of Tulsi (Ocimum Sanctum) from water. Issue 1 (16th August 2021) - Bayu, Kefelegn; Geremew, Abraham; Deriba, Wegene; Mulugeta, Yohannes; Wagari, Samuel; Dirirsa, Gebisa
Abstract: Fluoride concentration in drinking water higher than the recommended value imposes different health problems and there are advanced and chemical based defluoridation techniques, even if they are not feasible for developing countries and have limitations. Due to this, defluoridation by using locally available plants is one of the most efficient and sustainable options. Therefore, the current study was intended to investigate fluoride removal efficiency of Tulsi (Ocimum Sanctum) from water, which can be an alternative means to reduce the problem related to its high concentration. A laboratory-based experimental study was implemented by using potentiometric determination in Haramaya University. The leaves of Tulsi were collected, washed with tap water, rinsed with distilled water, and then dried at room temperature, crushed and sieved through a 500-μm stainless steel sieve. The experiments were conducted on water artificially fluoridated by anhydrous fluoride and natural water samples collected from deep well water sources from Adama and Harar town. Data was analyzed using Design of Expert (DOE) and Microsoft Excel. Twenty-nine runs for aqueous solution were conducted at different factor combinations and the optimum combinations were applied for natural water samples. The study depicts that the plant has an efficiency of removing 68.4% of fluoride from water. The best factor combinations to achieve this efficiency was 0.2 g/100 ml, 22.6 min, 5.7 and 6.6 mg/l, adsorbent dose, contact time, pH and initial concentration respectively. pH and initial concentration have a negative effect and adsorbent dose and contact time have a positive effect on removing fluoride from water. Hence, people living in fluorosis endemic areas can use the processed plant as a de-fluoridating agent to minimize adverse health effects. HIGHLIGHT: This research article paves the way to further study to remove contaminants from water, wastewater, which can pose a substantial effect on public health. The study was conducted to investigate the removal mechanism of fluoride from drinking water with a low cost, locally available plant and software technologies were applied to find the optimum conditions at which the adsorbent works best.